2018
DOI: 10.1080/09637486.2018.1446915
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index, bone health and body composition in a population of young adults: a cross-sectional study

Abstract: Diet quality has been postulated as a relevant factor in disorders like obesity and osteoporosis as it modulates inflammatory biomarkers. The aim of this study was to investigate whether the dietary inflammatory index (DII) is associated with bone health status and body composition parameters in a population of young adults. The study population consisted of 599 young adults (aged 20.41 ± 2.72). Linear regression analysis revealed that weight and fat-free mass (FFM) were significantly associated with the DII a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
1
20
4
Order By: Relevance
“…Therefore, the results of our study can be considered as one of the most important parts of the relationship between diet, inflammation, obesity and related diseases. In contrast to our study, Correa-Rodríguez et al reported that the inflammatory potential of diet, measured using the DII, is associated with obesity-related parameters such as fat-free mass and weight, but not with BMI and fat mass in adults [21]. It can be due to difference in the age of the participants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results of our study can be considered as one of the most important parts of the relationship between diet, inflammation, obesity and related diseases. In contrast to our study, Correa-Rodríguez et al reported that the inflammatory potential of diet, measured using the DII, is associated with obesity-related parameters such as fat-free mass and weight, but not with BMI and fat mass in adults [21]. It can be due to difference in the age of the participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, it has been also demonstrated that dietary inflammatory index is associated with body composition in Spanish adolescents [21]. The financial and nonfinancial costs imposed by obesity on the health system of the countries are dramatically significant [5,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have investigated the relationship between DII and obesity parameters, such as anthropometric measures and body composition. A recent study in Spain demonstrated that a higher DII score is signi cantly associated with decreased obesity-related parameters such as FFM and weight [31]. In contrast with the current study's results, previous papers have shown DII to be associated with higher average BMI, waist circumference, and WHR, after adjusting for known risk factors [32].…”
Section: Discussioncontrasting
confidence: 99%
“…Also, Camargo et al (2017) conducted a study on 90 overweight men and women with sedentary lifestyle, aimed to investigate the association between DII and heart risk factors, and the results indicated that there was no significant association between DII and weight, waist circumference, BMI, Obesity, overweight and body fat percentage (30). In their study, Cora et al, evaluated the association of DII with bone health and body composition in the young population, and the results showed no association between DII and BMI, fat percentage, muscle percentage and visceral fat, before and after adjusting for confounding factors (7). However, in a prospective study of Alam et al performed on 651 men, there was a direct and significant association between DII and weight, waist-to-hip ratio (WHR) and body fat percentage (16).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic differences can be seen depending on the location of the fat cells. For example, excessive fat accumulation in visceral adipose tissue is associated with higher health risks than subcutaneous fat accumulation (1,7).…”
Section: Introductionmentioning
confidence: 99%